“PROKRASTINASI MENGHAMBAT TUGASKU” (STUDI KORELASI: RENDAHNYA SELF EFICACY MENINGKATKAN PROKRASTINASI AKADEMIK MAHASISWA DALAM MENYELESAIKAN TUGAS PERKULIAHAN DI MASA PANDEMI COVID-19) - Husni Anggoro; Kemilau Senja Berlian Agustina; Eka Ananda Lintang Savitri; Fikri Ardiansyah Firnanda; Starry Kireida Kusnadi (Jurnal Gesi, 2023)
The purpose of this study was to see how the relationship between self-efficacy and student academic procrastination in completing lecture assignments during the COVID-19 pandemic. Self-efficacy is the most important thing in helping students to complete lecture assignments during the COVID-19 pandemic, the influence of self-efficacy on the individual's way of thinking will be able to direct encouragement and action to achieve a positive outcome for the individual himself. Meanwhile, academic procrastination in students can prevent them from completing a certain course. The longer they delay, the longer it will take them to complete the coursework. This research uses quantitative methods. The scale used is the self-efficacy scale adapted from research conducted by Mulia Sulistyowati, and the academic procrastination scale adapted from research conducted by Nova Emi Aliance Nainggolan. The subjects in this study were 116 students. The results of this study indicate that there is a negative relationshi this means that the lower the self-efficacy, the higher the student's academic procrastination and vice versa, the higher the self-efficacy, the lower the student's academic procrastination.Keywords: self-efficacy, academic procrastination, COVID-19